Mathematics
AniNurhalizah
2021-09-15 07:48:36
Let f(x) =4x-1 and g(x) = 2x^2 + 3 (fg)(x) , f/g(x), g/f(x)
ANSWERS
mickellehardy
2021-09-15 14:17:24

f(x) = 4x - 1 g(x) - 2x² + 3 (f · g)(x) (f · g)(x) = (4x - 1)(2x² + 3) (f · g)(x) = 4x(2x² + 3) - 1(2x² + 3) (f · g)(x) = 4x(2x²) + 4x(3) - 1(2x²) - 1(3) (f · g)(x) = 8x³ + 12x - 2x² - 3 (f/g)(x) (f/g)(x) = 4x - 1              2x² + 3 (g/f)(x) (g/f)(x) = 2x² + 3                4x - 1 (g/f)(x)= ¹/₂x + ¹/₈ +  3¹/₈                               4x - 1

ADD ANSWER